COMPARE KNOWLEDGE ON SELF CARE MANAGEMENT OF PREGNANCY INDUCED HYPERTENSION BETWEEN PRIMI GRAVID AND MULTIGRAVIDA - P., Prathima (Journal of Health and Allied Sciences NU, 2014)
Objectives: to assess and compare the knowledge on self-care management of pregnancy induced hypertension among primi gravid and multi gravida mothers.Method: A non-experimental descriptive comparative was conducted between 40 primi gravida mother and 40 multi gravida mothers who were selected by using purposive sampling to assess knowledge on self-care management of pregnancy induced hypertension. Self-structured questionnaire was used to collect the data. Appropriate Descriptive and inferential statistics were used to analyse data and to draw inferences.Results: 55% of primi gravida mothers and 40 % of multi gravid mothers had inadequate knowledge. Only 2.5% of primi gravida and 5% of multi gravida mothers had adequate knowledge. Respondents from primigravida had knowledge about 31.8 % and 38.6% regarding signs & symptoms and Preventive measures. 35% and 44.7 % of multi mothers were aware about signs & symptoms and preventive measures respectively. Which shows all the respondent were less aware about pregnancy induced hypertension. And there is an association between age & Monthly income on knowledge level.Conclusion: There is a necessity to provide information for those specific at risk population. Which helps to increase the knowledge, develop positive attitude, prevent complications and to have better maternal and child health.
Keywords: Pregnancy induced hypertension; Self-care management; HELLP and eclampsia